Resistin, an Adipokine with Non-Generalized Actions on Sympathetic Nerve Activity - Badoer, Emilio; Kosari, Samin; Stebbing, Martin J. (Frontiers in Physiology, 2015)
The World Health Organisation has called obesity a global epidemic. There is a strong association between body weight gain and blood pressure. A major determinant of blood pressure is the level of activity in sympathetic nerves innervating cardiovascular organs. A characteristic of obesity, in both humans and in animal models, is an increase in sympathetic nerve activity to the skeletal muscle vasculature and to the kidneys. Obesity is now recognised as a chronic, low level inflammatory condition and pro-inflammatory cytokines are elevated including those produced by adipose tissue. The most well known adipokine released from fat tissue is leptin. The adipokine, resistin,, is also released from adipose tissue. Resistin can act in the central nervous system to influence the sympathetic nerve activity. Here, we review the effects of resistin on sympathetic nerve activity and compare them with leptin. We build an argument that resistin and leptin may have complex interactions. Firstly, they may augment each other as both are excitatory on sympathetic nerves innervating cardiovascular organs; In contrast, they could antagonize each other’s actions on brown adipose tissue, a key metabolic organ. These interactions may be important in conditions in which leptin and resistin are elevated, such as in obesity.